The Frailty Phenotype in Older Adults Undergoing Cochlear Implantation. Issue 10 (3rd December 2022) - Kay-Rivest, Emily; Friedmann, David R.; McMenomey, Sean O.; Jethanamest, Daniel; Thomas Roland, J.; Waltzman, Susan B.
Abstract : Objective: To prospectively evaluate the frailty phenotype in a population of older adults and determine its association with 1) perioperative complications, 2) need for vestibular rehabilitation after surgery, and 3) early speech perception outcomes. Study Design: Prospective cohort study. Setting: Tertiary care hospital. Patients: Adults older than 65 years undergoing cochlear implantation. Interventions: The Fried Frailty Index was used to classify patients as frail, prefrail, or not frail based on five criteria: 1) gait speed, 2) grip strength, 3) unintentional weight loss, 4) weekly physical activity, and 5) self-reported exhaustion. Main Outcomes Measures: Rates of intraoperative and postoperative complications, postoperative falls, need for vestibular rehabilitation, and early speech perception outcomes. Results: Forty-six patients were enrolled in this study. Five patients (10.8%) were categorized as frail and 10 (21.7%) as prefrail. The mean ages of frail, prefrail, and not frail patients were 80.9, 78.8, and 77.5, respectively. There were no intraoperative complications among all groups. Three patients required postoperative vestibular rehabilitation; all were not frail. One postoperative fall occurred in a nonfrail individual. Mean (standard deviation) device use times at 3 months in frail, prefrail, and not frail patients were 7.6 (3.5), 11.1 (3.6), and 11.6 (2.9) hours per day, respectively. Consonant–nucleus–consonant word scores 3 months after surgery in frail, prefrail, and not frail patients were 13% (12.2), 44% (19.7), and 51% (22.4), respectively. The median (range) number of missed follow-up visits (surgeon, audiologist, speech language pathologist combined) was 7 (1–10) in frail patients, compared with a median of 3 (0–4) and 2 (0–5) in prefrail and not frail patients. Conclusions: Frail patients did not have increased rates of surgical complications, need for vestibular rehabilitation, or postoperative falls. However, frail patients experienced challenges in accessing postoperative care, which may be addressed by using remote programming and rehabilitation.